Pengaruh layanan penguasaan konten terhadap tingkatnya motivasi belajar pada siswa kelas VIII SMPN 01 Cileungsi - Rahayu Septiyanti Sukmana; Evi Fitriyanti; Fijriani Fijriani (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2019)
Motivation is very necessary in the learning process, because when students do not have the motivation to learn it can interfere with the process of learning activities. One service that can build student motivation in learning is content mastery services. The purpose of this study was to determine the Effect of Content Mastery Services on the Level of Learning Motivation in Class VIII Students of SMPN 01 Cileungsi. Research conducted using quantitative research, a quasi-experimental approach to the design of nonequivalent control group. The results of this study can be seen in the paired sample test results obtained by the Sig. (2-tailed) of 0,000 <0.05 means that there is a difference between learning motivation in the pre and post test data of each group. In the independent sample test, the Sig. (2-tailed) of 0.083> 0.05 means that there is no difference between the motivation of learning in the experimental and control groups. The conclusion is the content mastery service influences the level of learning motivation in class VIII students of SMPN 01 Cileungsi